Short-term effects of atropine combined with orthokeratology (ACO) on choroidal thickness. Issue 3 (June 2021) - Zhao, Wenchen; Li, Zhouyue; Hu, Yin; Jiang, Jinyun; Long, Wen; Cui, Dongmei; Chen, Weiyin; Yang, Xiao
Abstract: Purpose: To analyse the one-month change in subfoveal choroidal thickness (SFChT) of myopic children treated with 0.01 % atropine, orthokeratology (OK), or their combination. Methods: This is a prospective, randomized controlled trial. One hundred fifty-four children aged between 8 and 12 years with a spherical equivalent (SE) of -1.00 to -6.00 diopters were enrolled. Subjects were randomly assigned to receive 0.01 % atropine and orthokeratology (ACO, n = 39), 0.01 % atropine and single vision glasses (atropine, n = 42), orthokeratology and placebo (OK, n = 36), or placebo and single vision glasses (control, n = 37). SFChT was assessed using optical coherence tomography (OCT). Ocular parameters, including axial length (AL), were measured using a Lenstar LS 900. Results: SFChT significantly increased in the ACO (14.12 ± 12.88 μm, p < 0.001), OK (9.43 ± 9.14 μm, p < 0.001) and atropine (5.49 ± 9.38 μm, p < 0.001) groups, while it significantly decreased in the control group (-4.81 ± 9.93 μm, p = 0.006). The one-month change in SFChT was significantly different between the control and treatment groups (p < 0.001). The results of pairwise comparisons among the treatment groups showed that the magnitude of the SFChT change was larger in the ACO group than in the atropine group (p = 0.002). The changes in the ACO and OK groups were not significantly different (p = 0.326). Conclusion: The combination of OK and atropine induced a greater increase in SFChT than monotherapy with atropine, which might indicate a better treatment effect for childhood myopia control.